Nonlinear p-y analysis of laterally loaded piles - Lau, Wei Hing. (2008)
This report sets out to solve the finite difference equations of the lateral pile problem using an optimisation program, the standard Solver, which resides in Microsoft Excel, and compares the results with a similar constrained optimisation method by Low and Teh (2001) together with the results of analyses by Lpile through ten cases studies and examples, employing eight p-y curves of cohesive and cohesionless soil for both non-layered and layered soil strata, with four pile head boundary conditions.